The 4-Level Approach: Prevention of Suicidal Behaviour Through Community-Based Intervention - Hegerl, Ulrich; Heinz, Ines; O'Connor, Ainslie; Reich, Hanna (Frontiers in Psychiatry, 2021)
Due to the many different factors contributing to diagnostic and therapeutic deficits concerning depression and the risk of suicidal behaviour, community-based interventions combining different measures are considered the most efficient way to address these important areas of public health. The network of the European Alliance against Depression has implemented, in more than 120 regions within and outside of Europe, community-based 4-level-interventions that combine activities at four levels: i) primary care, ii) general public, iii) community facilitators and gatekeepers (e.g., police, journalists, care-givers, pharmacists, teachers), and iv) patients, individuals at high risk and their relatives. This review will discuss lessons learned from these broad implementation activities. These include targeting depression and suicidal behaviour within one approach; being simultaneously active on the four different levels; promoting bottom-up initiatives; and avoiding any cooperation with the pharmaceutical industry for reasons of credibility.